The lost daughter ebook - Ferrante, Elena (2008)
Now a major motion picture directed by Maggie Gyllenhaal and starring Olivia Colman, Dakota Johnson, Paul Mescal, and Peter Sarsgaard Another penetrating Neapolitan story from  New York Times– bestselling author of  My Brilliant Friend  and  The Lying Life of Adults. Leda, a middle-aged divorcée, is alone for the first time in years after her two adult daughters leave home to live with their father in Toronto. Enjoying an unexpected sense of liberty, she heads to the Ionian coast for a vacation. But she soon finds herself intrigued by Nina, a young mother on the beach, eventually striking up a conversation with her. After Nina confides a dark secret, one seemingly trivial occurrence leads to events that could destroy Nina’s family in this “arresting” novel by the author of the New York Times –bestselling Neapolitan Novels, which have sold millions of copies and been adapted into an HBO series ( Publishers Weekly ).   “Although much of the drama takes place in [Leda’s] head, Ferrante’s gift for psychological horror renders it immediate and visceral.” — The New Yorker   “Ferrante’s prose is stunningly candid, direct and unforgettable. From simple elements, she builds a powerful tale of hope and regret.” — Publishers Weekly